Author’s self-portrait in two stories written by Hakob Mndzuri - Avagyan, Artsrun (Bulletin of Yerevan University B: Philology, 2022)
The article refers for the first time to two stories by Hakob Mndzuri, which have not ever been presented to our readers by our literary critics.Mndzuri has always repeated that his works are right his biography. And indeed, Mndzuri is a person present, participating or acting in all his stories. This reality is especially visible in the two works under discussion, one of which is entitled “The Poet”, and the other – “The Poet and Money”. In the first, the writer introduces the poet “who lived centuries ago”, who is in fact himself, the evidence of which are all the attributions and images that he directs to that “poet”, but which are taken from Mndzuri’s stories. In the second story, the writer presents a “case” of a poet finding five gold coins on the street, which he does not spend finally, because no problem would be solved with that money, taking into consideration his concerns and needs.In both stories, Mndzuri raises ideas of human honesty and beauty, thus showing the true essence of an artist, a moral person.
Keywords: Mndzuri; poet; autobiography; village; art critic; memoir; depict; story; sock; tie; oven; to write; people; idea